THE APPLICATION OF THE PRINCIPLE OF EQUALITY BEFORE THE LAW IS REVIEWED FROM THE IMPLEMENTATION OF CROWD PUNISHMENT DURING THE COVID-19 PANDEMIC (CASE STUDY OF DECISION NUMBER 221/PID. SUS/2021/PN. JKT. TEAM) - Bustomy, Bustomy; Aman, Chairul; Jamilah, Jamilah (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The Covid-19 pandemic has had a significant impact on various aspects of life, including law enforcement in Indonesia. One of the problems that emerged was the application of the legal principle of equality before the law. This study aims to analyze the application of the principle of equality before the law during the Covid-19 pandemic still has weaknesses reviewed from Law Number 6 of 2018 concerning Health Quarantine, by taking a Case Study of Decision Number 221/Pid.Sus/2021/PN. Jkt. Team involving Habib Rizieq Shihab. The research method used is a qualitative approach with the type of case study research. Data were collected through document studies, interviews, and participatory observations. The analysis was carried out using content analysis techniques to identify problems with the effectiveness of law enforcement in cases of crowd crimes during the pandemic. The results of the study show that there is legal uncertainty in the enforcement of crimes against crowd violations during the pandemic. This uncertainty is caused by inconsistencies in the application of the law, lack of transparency in the law enforcement process, and differences in legal interpretation at various levels of court. The case of Habib Rizieq Shihab revealed that there was different treatment in law enforcement, which caused a perception of injustice in society. This study suggests several steps to apply the principle of equality before the law for violators of criminal sanctions. First, consistent and indiscriminate law enforcement is needed to maintain public trust in the legal system. Second, transparency in the law enforcement process must be improved, including the delivery of clear information regarding detention procedures and sanctions given. Third, the government and related institutions need to increase public awareness of the importance of complying with health protocols through effective education campaigns. Fourth, evaluation and revision of policies related to the handling of crowd crimes must be carried out periodically to adjust to the current situation and conditions and accommodate inputs from various parties, which is expected to increase the accuracy in criminalizing crowds during the Covid-19 pandemic, so as to create justice and legal certainty.